Association of aromatase with bladder cancer stage and long-term survival: new insights into the hormonal paradigm in bladder cancer - Nguyen, Daniel P.; O'Malley, Padraic; Al Hussein Al Awamlh, Bashir; Furrer, Marc-Alain; Mongan, Nigel P.; Robinson, Brian D.; Wang, Gerald J.; Scherr, Douglas S. (Elsevier, 2017)
BACKGROUND